Critical review on the relationship between design variables and performance of dexterous hands: a quantitative analysis - Jiang, Lei; Fu, Chaojie; Liang, Yanhong; Jin, Yongbin; Wang, Hongtao (Frontiers in Neurorobotics, 2025)
Dexterous hands play vital roles in tasks performed by humanoid robots. For the first time, we quantify the correlation between design variables and the performance of 65 dexterous hands using Cramér’s V. Comprehensive cross-correlation analysis quantitatively reveals how the performance, such as speed, weight, fingertip force, and compactness are related to the design variables including degrees of freedom (DOF), structural form, driving form, and transmission mode. This study shows how various design parameters are coupled inherently, leading to compromise in performance metrics. These findings provide a theoretical basis for the design of dexterous hands in various application scenarios and offer new insights for performance optimization.